The relationship between iron nutrition and the factors present in vegetable and cereal foods that affect iron absorption - Gillooly, Mary . A. (My University, 1986)
The iron nutrition of populations is largely determined by the quality of the diet consumed. As this is frequently cereal or vegetable based, the interplay of the different enhancers and inhibitors that influence iron absorption from the "common pool" of non-haem iron assumes a profound significance in iron nutrition. This thesis took advantage of the widespread occurrence of iron deficiency among Indian women in Natal to establish more clearly the factors in frequently consumed foods which affect iron absorption.
A thesis submitted to the Faculty of Medicine, University of the Witwatersrand, Johannesburg, for the Degree of Doctor of Philosophy in Medicine. Johannesburg, 1986
Keywords: Iron; Absorption; Edible Grain; Vegetables